Verónica Gerber Bicecci, La compañía (Ciudad de México, Almadía, 2019, 199 pp. ISBN 978-607-8667-10-9) (Altre Modernità, 2020)
Verónica Gerber Bicecci, La compañía (Ciudad de México, Almadía, 2019, 199 pp. ISBN 978-607-8667-10-9)por Federico Cantoni